Evaluating the Atrial Myopathy Underlying Atrial Fibrillation. Issue 4 (28th July 2015) - Goldberger, Jeffrey J.; Arora, Rishi; Green, David; Greenland, Philip; Lee, Daniel C.; Lloyd-Jones, Donald M.; Markl, Michael; Ng, Jason; Shah, Sanjiv J.
<x xml:space="preserve">Abstract</x> Atrial disease or myopathy forms the substrate for atrial fibrillation (AF) and underlies the potential for atrial thrombus formation and subsequent stroke. Current diagnostic approaches in patients with AF focus on identifying clinical predictors with the evaluation of left atrial size by echocardiography serving as the sole measure specifically evaluating the atrium. Although the atrial substrate underlying AF is likely developing for years before the onset of AF, there is no current evaluation to identify the preclinical atrial myopathy. Atrial fibrosis is 1 component of the atrial substrate that has garnered recent attention based on newer MRI techniques that have been applied to visualize atrial fibrosis in humans with prognostic implications regarding the success of treatment. Advanced ECG signal processing, echocardiographic techniques, and MRI imaging of fibrosis and flow provide up-to-date approaches to evaluate the atrial myopathy underlying AF. Although thromboembolic risk is currently defined by clinical scores, their predictive value is mediocre. Evaluation of stasis via imaging and biomarkers associated with thrombogenesis may provide enhanced approaches to assess risk for stroke in patients with AF. Better delineation of the atrial myopathy that serves as the substrate for AF and thromboembolic complications might improve treatment outcomes. Furthermore, better delineation of the pathophysiologic mechanisms underlying the development of the atrial substrate for AF, particularly in its earlier stages, could help identify blood and imaging biomarkers that could be useful to assess risk for developing new-onset AF and suggest specific pathways that could be targeted for prevention.